Optimizing energy efficiency in cement production: The role of IIoT in sustainable manufacturing practices - Alyousefi, Ahmed Mahmood Abdulhameed Abdullah; Cahyari, Khamdan (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
One of the most energy-intensive businesses, cement has major environmental effects from high carbon emissions. Adoption of Industrial Internet of Things (IIoT) technologies offers a workable way to maximize cement production, improve energy economy, and lower running expenses. The contribution of Industry 4.0 technologies—including IoT, artificial intelligence (AI), big data analytics, and cyber-physical systems—in changing cement manufacturing processes is investigated in this work. By means of a methodical assessment of secondary data sources, the study reveals important advantages, difficulties, and sustainability initiatives connected to IIoT deployment. The results imply that even if IIoT greatly increases production efficiency and lowers emissions, issues including high implementation costs and cybersecurity threats have to be taken care of. For industry players, legislators, and academics trying to propel digital change in cement production, the study offers useful information.